ANALISIS PERBANDINGAN TINGKAT EFISIENSI BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL DI INDONESIA (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bank Indonesia Tahun 2011-2013) - Reza Adi Nugraha; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2016)
This study aims to determine the differences between Islamic banks with conventional banks are based on the level of efficiency of each type financial institutions in the period 2011-2013 in Indonesia.This study using the Data Envelopment Analysis in determining the values of efficiency at each banking company that is used as a sample in the study. The sample used in this study was 22 banking companies of which consists of 11 islamic banks and 11 other samples are conventional commercial banks, each of which is a bank of the same category and has total assets most closely with their respective Islamic banks in 2011. The sample was determined by purposive sampling method with certain and considerations. The data used in this research is secondary data obtained from financial statements published by each bank. Data obtained from the financial statements of each bank is used to measure the efficiency of each bank. After each bank efficiency values are known, the values are then analyzed using independent sample t-test.The results showed that the test based on independent sample t-test, the efficiency of each type of banking does not have significant differences. The tesults of this research in line with several pervious studies which showed that there was no significant difference in the level of efficiency in the banking institutions that use Islamic basis and conventional banking institutions.